Cognitive and Emotional Drivers of Online Purchase Decisions in Live-Streaming Social Commerce - Devangga Putra Adhitya Pratama; Syamsul Arifin; Ardhita Eko Ginanjar; Kurniawati Kurniawati (CV Pena Jaya Pers, 2025)
Purpose: This study examines how cognitive and emotional drivers jointly shape online purchase decisions in live-streaming social commerce, focusing on consumers’ real-time decision-making experiences. Design/methodology/approach: A qualitative descriptive–interpretive approach was employed using in-depth semi-structured interviews with consumers who had made purchases through live-streaming sessions. Data were analyzed thematically using NVivo to identify dominant cognitive and emotional patterns. Findings: The findings reveal that purchase decisions are formed through the simultaneous interaction of rapid cognitive evaluations (information clarity, perceived value, trust) and emotional triggers (FOMO and parasocial interaction), with platform affordances accelerating this process. Research limitations/implications: This study is limited by a small sample size and a single-country context, which may restrict generalizability. Practical implications: The results suggest that live-streaming strategies should balance emotional engagement with credible information to sustain trust and satisfaction. Originality/value: This study offers an integrated cognitive–emotional perspective on live-streaming purchase decisions.